Isaiah Thomas correspondence - Thomas, Isaiah, 1749-1831.
ALsS relating to Thomas's printing business in Worcester, Mass. Correspondents include William Bentley Fowle, George Thacher, and John West.
Printer and newspaper publisher.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Fowle, William Bentley, -- 1795-1865 -- Correspondence; Thacher, George, -- 1754-1824 -- Correspondence; West, John, -- 1770-1827 -- Correspondence; Printing industry -- Massachusetts -- Worcester; Printers; Publishers